Improving Supply Chain Management Efficiency in Fashion: AHP-Based Vendor Selection - Alhamda, Nur Aini; Darmawan, Bambang; Dwiyanti, Vina (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
In an increasingly competitive industrial world, selecting the right vendor is crucial for maintaining the quality and continuity of a company's operations. This study was conducted at PT Bersama Zatta Jaya Tbk, a company engaged in the Muslim fashion industry, to evaluate and determine the best vendor for the